PENGARUH PEMBERIAN BAHAN ORGANIK KIRINYU ( Chromolaena Odorata )TERHADAP PERTUMBUHAN DAN HASIL SAWI (Brasica Juncea ) DI KAWASAN AGROECOTOURISM - Agustinus JP Ana saga; Murdaningsih Murdaningsih (AGRICA, 2011)
This study aimed to explore the effect of Siam weed (Chromolaena odorata) green manure application on the growth and development of mustard (Brassica juncea) in Kelimutu National Park, Indonesia. The study was carried out between September and November 2010 in Ende district on the island of Flores, Indonesia, at an altitude of 1500 to 1730 meters above sea level. This study used a randomized block design with four treatments: K0: No Siam weed application, K1: 5 tons/ha Siam weed (2.8kg/plot), K2: 10 tons/ha Siam weed (5.6kg/plots), K3: 15 tons/ha Siam weed (8.4kg/plot), K4: 20 tons/ha Siam weed (11.2kg/plot). Researchers observed plant characteristics (plant height, leaf area, wet weight and number of leaves) and soil fertility indicators (Organic carbon). Plant organic matter was ground and subsequently analyzed for nutrients using a randomized block design along with lab analysis for soil fertility. The results of this study showed that the application of Siam weed organic matter had no significant effect on mustard plant height, leaf number, leaf area, or wet weight. However, it was found that organic matter application did have a significant effect on soil fertility indicators (organic carbon), and caused an increase in soil organic matter content.